Requirements for teachers in the context of postgraduate nursing education: Polish experiences - Dorota Ozga; Wioletta Mędrzycka-Dąbrowska; Aleksanda Gutysz-Wojnicka; Asta Heikkilä; Leena Salminen (Czech Republic, 2025)
The competency of nurse teachers and collaboration between nurse educators, nurse leaders and mentors are crucial for achieving high-quality Evidence-Based nursing education. The profession of a nurse teacher is one of public trust and it requires the integration of skills, attitudes, standards, and theoretical knowledge as well as awareness of individual, organisational and social circumstances. The data were collected via email using a structured questionnaire (A Tool for the Evaluation of Requirements of a Nurse Teacher). The respondents' evaluation of the professional competencies and the overall rating correlated with their age. Older age corresponded to higher scores in professional and teaching competencies, in personality factors, and to a higher general ERNT score (p = 0.019). The lowest scores were awarded for teaching competencies - which shows that postgraduate education should be more closely monitored in this respect. The tool for the Evaluation of Requirements of a Nurse Teacher (ERNT) designed for the needs of nurse education can also be implemented in the evaluation of postgraduate education of nurses and midwives.